An induced pluripotent stem cell line derived from a patient with neonatal diabetes and Fanconi-Bickel syndrome caused by a homozygous mutation in the SLC2A2 gene - Ahmed K. Elsayed (13275302) (2021)
Recessive mutations in the glucose transporter gene SLC2A2 (GLUT2) lead to permanent neonatal diabetes (PNDM) and Fanconi Bickel Syndrome (FBS). Here, we generated an induced pluripotent stem cell (iPSC) line, QBRIi012-A, from a 24-month-old boy with FBS and PNDM due to homozygous nonsense mutation in the SLC2A2 gene (c.901C > T). The QBRIi012-A was fully characterized using different approaches. The cell line showed normal karyotype and was able to differentiate into the three germ layers in vitro. This iPSC line provides a novel human cell model to understand the pathophysiology of FBS and diabetes associated with SLC2A2 defects. Other Information Published in: Stem Cell Research License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.scr.2021.102433 Additional institutions affiliated with: Diabetes Research Center - QBRI